The Use of Electroshock Weapons by the Finnish Police in 2016 - Henri Rikander (Nordisk Tidsskrift for Kriminalvidenskab)
When using force, police officers also exercise public power and thereby interfere in a significant way with people’s basic legal and human rights. This article examines situations in which Finnish police officers use electroshock weapons as a means of force. The material for the study consists of all (N=357) reports on the use of force involving electroshock weapons for the year 2016. Over half of the police tasks where electroshock weapons were used were connected to the  rotection of individual life and health. The majority of these situations occurred during the evening and at night. Every fourth application of an electroshock weapon took place in a private residence while every tenth occurred within police facilities. By threatening to use an electroshock weapon, the desired result was attained in one out of five situations. Of all situations where an electroshock weapon was used, 88% transpired without injuries to persons or property. The police officers using these electroshock weapons were experienced and had received regular training in their use. The discussion surrounding the use of electroshock weapons is divided between the negative stance taken by human rights  organizations and the positivestance taken by authorities who strive to equip the police with as appropriate means of force as possible. The current article contributes to the Finnish, Nordic, and European discussions of, among other things, the proper hierarchical position of electroshock weapons as a means of force available to police. It also explores questions surrounding police competence to use these weapons and matters relating to their actual use.